A moment in time [large type] - Peterson, Tracie (Peterson, Tracie. Lone Star brides, 2014)
Alice Chesterfield is a woman pursued. Having survived an attack that left her scarred and her father dead, she is never free from the fear and memories of the man who is responsible. Texas seems to be an answer to Alice's prayers, and when she has the opportunity to relocate to a ranch near Dallas, Robert Barnett captures her attention. Unlike any man Alice has ever known, Robert doesn't worry about the obstacles that stand in their way -- and he hardly seems to notice the scar she bears. But there are storm clouds gathering; devastating information about her family comes to light, threatening Alice's peaceful sanctuary. Disillusioned, Alice must learn to place her trust in God as she seeks a measure of peace for her future... and for her heart.